Protestantism, ethnicity and class in Chimborazo - Muratorio, Blanca (1981)
Although discussion of the folk Catholicism of Andean Indian peasants has a long tradition in the anthropological literature, onlv a few social scientists1 have dealt with the problem of Protestantism in South America. Their studies have focused either on large urban centers in Brazil, Chile (Willems 1967, Lalive D'Espinay 1969), and Colombia (Flora 1976) or on relatively small Indian populations in the Brazilian tropical forest (Ribeiro 1973) and the Argentine Chaco (Miller 1971, 1974, 1975). This paper examines the emergence and development of evangelical Protestantism among a group of Indian peasants in the Ecuadorian highlands. These Indian peasants still preserve fundamental aspects of their culture and social organization, although they have been for more than 400 years an integral part of a class society as semiserfs and now as freeholders. Consequently, I will discuss the effects of the adoption of Protestantism on both ethnic and class consciousness.